Time-Modulated Array-Based Rotating Electric-Field Vector Method for Extracting Angle Information - Geon U Kim; Sang-Hwa Yi; Jeong Phill Kim (IEEE Access)
This study proposes the time-modulated array (TMA) based rotating electric-field vector (REV) method as a means of extracting the angle information of the incoming fully correlated signals. By varying the delay parameter of the TMA signal, the REV signal can be formed, and its maximum or minimum can be used to extract the target angle. Furthermore, the target angle can be extracted by applying the inverse discrete Fourier transform to successive uniform samples of the first harmonic of the REV signal. Compared to the method that employs the magnitude ratios of the fundamental and harmonic components, the proposed method requires only the magnitude of the first harmonic component. Moreover, the angle information extracted is unambiguous. Additionally, this method can be extended to multiple target cases with the aid of a multi-element TMA and a complex REV method. In this case, inverse filtering is adopted to provide a higher angular resolution with a small loss in signal-to-noise ratio. An error analysis for the proposed method was performed by numerical simulation, and both the simulated and experimental results of the TMA-REV system fully validated the proposed method.